Katecheza o grzechu Kaina na podstawie perykopy z Rdz 4,1-16 - Adamczyk, Dariusz (Studia Pastoralne, 2026)
Cain selfishly negated differentiation in the world, which was established by God. He lacked an appropriate relationship with himself. He didn’t overcome evil tendencies, didn’t gain control over sin and allowed himself to commit murder. Breaking our relationship with God leads to injustice in relations with others. Even after his sin, God attempts to re-establish dialogue with Cain, who however again turns out to be hardened toward God’s voice. For his sin he is cursed and outcast. God still promises him protection and places a mark upon him. Because He wants the conversion of the sinner more then his death. God gives him a chance for transformation.